Letter from Charles Ferris to James Curtis Booth, June 9, 1856 - Ferris, Charles (1856)
Request for information as regards to the determination of phosphoric acid by ammonium molybdate.
Keywords: Booth, James Curtis, 1810-1888; Phosphoric acid; Organic compounds--Synthesis; Chemistry teachers